Polyurethane-carbon nanotube composite modified asphalt mixture and preparation method thereof
By using polyurethane-carbon nanotube composite modifier in asphalt, the shortcomings of traditional asphalt materials in high temperature stability and fatigue crack resistance are solved, and the comprehensive performance of asphalt mixture is significantly improved, including high temperature stability and low temperature toughness, meeting the higher requirements of modern road engineering.
Patent Information
- Application Number
- CN202510075544.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
AI Technical Summary
传统沥青材料在高温稳定性和疲劳抗裂性方面存在不足,尤其在低温条件下韧性较差,难以满足现代道路工程对高温稳定性和疲劳抗裂性的更高要求。
The asphalt is modified by using polyurethane-carbon nanotube composite modifier. Through the synergistic action of polyurethane and carbon nanotubes, the mechanical properties and toughness of the asphalt mixture are improved, including tensile strength, compressive strength and low-temperature crack resistance.
It significantly improves the high-temperature stability, rut resistance, fatigue crack resistance and low-temperature toughness of the asphalt mixture, extends the fatigue life of the road surface, and improves the performance adaptability of the materials under complex service conditions.
Smart Images

Figure BDA0005246972710000041 
Figure BDA0005246972710000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a polyurethane-carbon nanotube composite modified asphalt mixture and a preparation method thereof. Background Art
[0002] Asphalt pavement is an important part of modern transportation infrastructure, and its mechanical properties directly affect the service quality and service life of the road. However, in actual applications, asphalt mixtures often face problems such as high-temperature rutting, fatigue cracking, and water damage. These diseases significantly reduce the structural strength and durability of the pavement, posing huge challenges to road maintenance and management. Especially in hot seasons, traffic loads can cause significant plastic deformation of asphalt mixtures, manifested as rutting. At the same time, the accumulation of long-term traffic loads can also cause fatigue cracks, further weakening the overall performance of the pavement structure. With the continuous increase in traffic volume and load levels, traditional asphalt materials and modification technologies have been unable to meet the higher requirements of modern road engineering for high-temperature stability and fatigue crack resistance.
[0003] Commonly used modifiers such as SBS (styrene-butadiene-styrene block copolymer) and rubber can improve the mechanical properties of asphalt mixtures to a certain extent, enhance their high temperature rutting resistance and fatigue resistance, but they are still insufficient in dealing with complex traffic conditions and long-term service environments. Especially under heavy-load traffic, the performance improvement effect of traditional modifiers is limited, and it is difficult to fully solve the above problems. This has prompted people to explore new modified materials to further improve the comprehensive performance of asphalt mixtures.
[0004] As a new type of asphalt modifier, polyurethane (PU) has received more and more attention and application research in recent years. Its unique molecular structure and excellent physical and chemical properties enable it to significantly improve the mechanical properties of asphalt mixtures, especially in terms of high temperature stability, rutting resistance, fatigue crack resistance and water stability. In addition, polyurethane modified asphalt mixtures also have good environmental adaptability and durability, showing a wide range of engineering application prospects. However, the performance of polyurethane modified asphalt materials under low temperature conditions is still insufficient. Its toughness is poor, its deformation capacity is limited, and it is easy to cause low-temperature cracking, which limits its promotion and use in cold areas.
[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a polyurethane-carbon nanotube composite modified asphalt mixture and a preparation method thereof, which further improves the toughness and deformation capacity of the material while ensuring excellent performance such as high temperature stability and fatigue crack resistance, so as to meet the performance requirements under various complex service conditions, promote the development of asphalt pavement material technology, and provide a new solution to solve road disease problems.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A polyurethane-carbon nanotube composite modified asphalt mixture, comprising composite modified asphalt, mineral aggregate and filler;
[0009] The composite modified asphalt accounts for 4% to 6% of the total weight of mineral aggregate and filler;
[0010] The composite modified asphalt is prepared by modifying asphalt with a polyurethane-carbon nanotube composite modifier, and the mass ratio of the polyurethane-carbon nanotube composite modifier to the asphalt is 20 to 25:100. Preferably, the mass ratio of the polyurethane-carbon nanotube composite modifier to the asphalt is 23:100. This mass ratio is selected based on the results of previous tests. At this mass ratio, the modified asphalt mixture exhibits the best performance balance, that is, while ensuring excellent mechanical strength and high temperature performance, it also ensures toughness at low temperatures.
[0011] In the present invention, polyurethane can significantly improve the mechanical properties of asphalt materials, including tensile strength and compressive strength, and carbon nanotubes provide excellent toughness and ductility, forming a complementary effect with polyurethane, so that the mixture exhibits better bearing capacity under heavy load and high stress conditions.
[0012] Furthermore, the preparation method of the composite modified asphalt includes:
[0013] (1) heating the base asphalt to 160° C. to obtain liquid asphalt;
[0014] (2) The polyurethane-carbon nanotube composite modifier is mixed with liquid asphalt, and high-temperature shearing is performed at 170-180° C. and a shear rate of 3000-4000 rpm for 60-90 minutes to obtain a composite modified asphalt.
[0015] Asphalt is easy to soften or deform under high temperature conditions, but the rigid skeleton structure of the cured polyurethane polymer significantly improves the high-temperature deformation resistance of the composite asphalt. Carbon nanotubes give asphalt higher crack resistance in low temperature environments, reducing the brittle cracking phenomenon of asphalt mixtures under low temperature conditions. The addition of composite modifiers improves the viscoelasticity of asphalt, allowing it to exhibit better rheological properties in a wide temperature range and adapt to road requirements under different climatic conditions.
[0016] Furthermore, the polyurethane-carbon nanotube composite modifier is made of polyisocyanate, polyol and carbon nanotubes through twin-screw extrusion. In the polyurethane-carbon nanotube composite modifier, the carbon nanotube content is 12% to 15%. The carbon nanotubes are combined with the polyisocyanate and polyol through chemical bonds and physical intercalation to form a toughness-rigidity complementary network structure, thereby enhancing the impact resistance and ductility of the composite material. The reinforced network formed by the 12% to 15% carbon nanotube content not only improves the overall toughness, but also ensures that the material has sufficient buffering capacity under high stress.
[0017] Furthermore, the preparation method of the polyurethane-carbon nanotube composite modifier comprises:
[0018] 1) Add polyol and carbon nanotubes into the main silo in proportion, and add polyisocyanate into the auxiliary silo alone;
[0019] The reaction of polyisocyanate (-NCO) and polyol (-OH) can occur at a relatively low temperature and is an exothermic reaction. If the two are directly heated after mixing, the reaction may be out of control and even cause gelation problems. The present invention adds polyisocyanate separately to the auxiliary silo, and can accurately control the start and rate of the reaction during the heating and mixing process, ensuring that the formation process of polyurethane is more controllable.
[0020] In the main silo, carbon nanotubes and polyols can be fully contacted and dispersed. Polyols usually have a lower viscosity and can more effectively coat carbon nanotubes, reducing the agglomeration of carbon nanotubes through shear force, while the subsequent addition of isocyanate can further coat the carbon nanotubes in the polyurethane network to form a strong interface bond.
[0021] 2) The screw speed of the twin-screw extruder is set between 100 and 300 rpm, and the temperature is set to a gradually increasing gradient, covering a temperature range of 120 to 160° C., and staged heating is performed; wherein the temperature of the first stage is set to 120 to 140° C. to achieve preliminary mixing of the polyol and the carbon nanotubes, and the temperatures of the second, third, fourth, and fifth stages are set to 140 to 160° C. to promote the reaction between the isocyanate and the polyol.
[0022] The segmented heating and screw shearing action make the carbon nanotubes more evenly dispersed in the polyurethane matrix, avoiding the problem of weakened toughness enhancement effect caused by carbon nanotube agglomeration. The evenly dispersed carbon nanotubes form a continuous network, significantly improving the low-temperature toughness of the composite material.
[0023] 3) After the mixture is melt-kneaded, it is granulated and dried to obtain a polyurethane-carbon nanotube composite modifier.
[0024] Furthermore, the carbon nanotubes are multi-walled carbon nanotubes with a diameter ranging from 10 to 50 nm and a length ranging from 1 to 10 μm. The carbon nanotubes are pre-treated with hydrogen peroxide (H2O2), which reacts with the carbon nanotubes at high temperature or under appropriate conditions to oxidize their surfaces and introduce hydroxyl groups on their surfaces, thereby enhancing their compatibility with polyurethane, achieving better interface adhesion, effectively transmitting loads, reducing interface slippage, and improving the mechanical properties of the composite material.
[0025] Furthermore, the polyisocyanate is one or more of methylene diphenyl diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate.
[0026] Furthermore, the polyol is one or more of polypropylene glycol, polyethylene glycol, and castor oil.
[0027] Preferably, the polyisocyanate is methylene diphenyl diisocyanate and the polyol is polypropylene glycol. Methylene diphenyl diisocyanate is selected because it is a commonly used polyisocyanate for preparing polyurethane, and it has an aromatic ring structure, provides a higher molecular polarity, can produce a stronger interaction with carbon nanotubes, and improves system stability. And the rapid reactivity of MDI ensures that a stable polyurethane matrix can be formed during extrusion. The reason why the polyol is selected as polypropylene glycol is that it is a polyether polyol, and its long chain structure can coat and disperse nanotubes, thereby reducing the van der Waals force between carbon nanotubes and preventing agglomeration. At the same time, polypropylene glycol, as a polyether polyol, can increase the flexibility of the overall composite modifier.
[0028] Furthermore, the particle size of the mineral aggregate is ≥ 0.075 mm, and the mineral aggregate is one or more of basalt, limestone and granite. This helps to increase the strength and stability of the mixture. The presence of coarse aggregate makes the mixture less likely to deform when subjected to external pressure, thereby enhancing its compression resistance, fatigue resistance and shear resistance.
[0029] Furthermore, the particle size of the filler is less than 0.075 mm, and the filler is one or more of basalt powder, limestone powder and granite powder. The filler can be derived from powder ground from mineral aggregates, and plays a filling role in the mixture. It can effectively fill the gaps between coarse particles, increase the density of the mixture, and thereby improve the material's anti-permeability and anti-aging properties.
[0030] Preferably, the gradation of mineral aggregate and filler is AC-13, which can effectively balance the ratio of coarse aggregate and fine aggregate, making the mixture more uniform during construction and reducing the construction difficulty caused by uneven particles.
[0031] Furthermore, a method for preparing a polyurethane-carbon nanotube composite modified asphalt mixture comprises the following steps:
[0032] S1. Pre-dry the mineral aggregates and fillers at 170-180°C for 2-3 hours. The mineral aggregates and fillers after drying are looser, reducing moisture that may cause uneven mixing, ensuring good bonding between modified asphalt and aggregates, and helping to improve uniformity in the subsequent mixing process.
[0033] S2. Heat and mix the composite modified asphalt and mineral aggregate at 170-180° C. for 3-5 minutes to obtain a mixture; this helps the composite modified asphalt to fully melt at a higher temperature, enhances the bonding force between the asphalt and the mineral aggregate, ensures that the modified asphalt can evenly cover the mineral aggregate, avoids asphalt stratification, and improves the stability of the mixture.
[0034] S3. Add fillers and continue mixing for 2 to 3 minutes to obtain a polyurethane-carbon nanotube composite modified asphalt mixture. By adding fillers to fill the gaps between mineral aggregates, the density of the mixture is improved, thereby improving the compressive strength and durability of the material.
[0035] The beneficial effects of the present invention are:
[0036] The present invention prepares a polyurethane-carbon nanotube composite modifier by twin-screw extrusion of polyisocyanate, polyol and carbon nanotubes, and then modifies asphalt with the composite modifier to prepare a modified asphalt mixture. The synergistic effect of polyurethane-carbon nanotubes enables the modified asphalt to more effectively disperse and absorb the stress caused by repeated loads, delay the initiation and expansion of fatigue cracks, and thus significantly extend the fatigue life of the road surface.
[0037] In the present invention, the twin-screw extrusion process can achieve uniform dispersion of carbon nanotubes in a polyurethane matrix under high shear conditions, ensuring the uniformity and stability of the composite modifier. The segmented heating control and screw speed adjustment can accurately control the reaction rate and mixing state, avoiding agglomeration of carbon nanotubes or incomplete reaction. The modifier particles are uniformly mixed with the asphalt matrix under high temperature conditions, can quickly disperse and react, and improve the modification efficiency. The granular design of the polyurethane-carbon nanotube composite modifier is convenient for storage and transportation, thereby improving the flexibility and applicability of industrial production. DETAILED DESCRIPTION
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0039]
[0040]
[0041] Example 1
[0042] A polyurethane-carbon nanotube composite modified asphalt mixture comprises composite modified asphalt, granite aggregate and filler; the composite modified asphalt accounts for 5% of the sum of the weight of the granite aggregate and the filler; the mass ratio of the aggregate to the filler is 92:8; the composite modified asphalt is prepared by modifying asphalt with a polyurethane-carbon nanotube composite modifier, and the mass ratio of the polyurethane-carbon nanotube composite modifier to asphalt is 23:100.
[0043] Furthermore, the preparation method of the composite modified asphalt includes:
[0044] (1) heating the base asphalt to 160° C. to obtain liquid asphalt;
[0045] (2) The polyurethane-carbon nanotube composite modifier is mixed with liquid asphalt, and high-temperature shearing is performed at 180° C. and a shear rate of 4000 rpm for 60 minutes to obtain a composite modified asphalt.
[0046] Furthermore, the polyurethane-carbon nanotube composite modifier is prepared by extruding methylene diphenyl diisocyanate, polypropylene glycol and multi-walled carbon nanotubes via a twin-screw extruder. The preparation method of the polyurethane-carbon nanotube composite modifier comprises:
[0047] 1) Add polyol and carbon nanotubes into the main silo in proportion, and add polyisocyanate into the auxiliary silo alone;
[0048] 2) The screw speed of the twin-screw extruder is set to 200 rpm, and the temperature is set to a gradually increasing gradient, covering a temperature range of 120 to 180° C., and heating is performed in sections;
[0049] 3) After the mixture is melt-kneaded, it is granulated and dried to obtain polyurethane-carbon nanotube composite modifier particles with a diameter of about 2 to 3 mm.
[0050] Furthermore, a method for preparing a polyurethane-carbon nanotube composite modified asphalt mixture comprises the following steps:
[0051] S1. Dry the granite aggregate and filler at 180°C for 3h in advance;
[0052] S2. Heat and mix the composite modified asphalt with granite aggregate at a mass ratio of 5% at 180° C. for 3 minutes to obtain a mixture; add filler and continue mixing for 2 minutes to obtain a polyurethane-carbon nanotube composite modified asphalt mixture.
[0053] The parameters of the prepared polyurethane-carbon nanotube composite modified asphalt mixture are shown in Table 1.
[0054] Table 1
[0055] project unit Test results Require Test specifications Marshall Strength kN 42.3 / JTG T 0709 Freeze-thaw splitting strength ratio % 96 80 JTG T 0729 Indirect tensile strength MPa 1.68 / AASHTO 322 Dynamic stability mm / times 12254 >3200 JTG F40-2004 Low temperature complete destruction strain με 3402 >2500 JTG T 0715
[0056] Example 2
[0057] A polyurethane-carbon nanotube composite modified asphalt mixture comprises composite modified asphalt, granite aggregate and filler; the composite modified asphalt accounts for 5% of the sum of the weight of the granite aggregate and the filler; the mass ratio of the aggregate to the filler is 92:8; the composite modified asphalt is prepared by modifying asphalt with a polyurethane-carbon nanotube composite modifier, and the mass ratio of the polyurethane-carbon nanotube composite modifier to asphalt is 20:100.
[0058] Furthermore, the preparation method of the composite modified asphalt includes:
[0059] (1) heating the base asphalt to 160° C. to obtain liquid asphalt;
[0060] (2) The polyurethane-carbon nanotube composite modifier is mixed with liquid asphalt, and high-temperature shearing is performed at 180° C. and a shear rate of 4000 rpm for 60 minutes to obtain a composite modified asphalt.
[0061] Furthermore, the polyurethane-carbon nanotube composite modifier is prepared by extruding methylene diphenyl diisocyanate, polypropylene glycol and multi-walled carbon nanotubes via a twin-screw extruder. The preparation method of the polyurethane-carbon nanotube composite modifier comprises:
[0062] 1) Add polyol and carbon nanotubes into the main silo in proportion, and add polyisocyanate into the auxiliary silo alone;
[0063] 2) The screw speed of the twin-screw extruder is set to 200 rpm, and the temperature is set to a gradually increasing gradient, covering a temperature range of 120 to 180° C., and heating is performed in sections;
[0064] 3) After the mixture is melt-kneaded, it is granulated and dried to obtain polyurethane-carbon nanotube composite modifier particles with a diameter of about 2 to 3 mm.
[0065] Furthermore, a method for preparing a polyurethane-carbon nanotube composite modified asphalt mixture comprises the following steps:
[0066] S1. Dry the granite aggregate and filler at 180°C for 3h in advance;
[0067] S2. Heat and mix the composite modified asphalt with granite aggregate at a mass ratio of 5% at 180° C. for 3 minutes to obtain a mixture; add filler and continue mixing for 2 minutes to obtain a polyurethane-carbon nanotube composite modified asphalt mixture.
[0068] The parameters of the prepared polyurethane-carbon nanotube composite modified asphalt mixture are shown in Table 2.
[0069] Table 2
[0070] project unit Test results Require Test specifications Marshall Strength kN 41.7 / JTG T 0709 Freeze-thaw splitting strength ratio % 95 80 JTG T 0729 Indirect tensile strength MPa 1.62 / AASHTO 322 Dynamic stability mm / times 11437 >3200 JTG F40-2004 Low temperature complete destruction strain με 3258 >2500 JTG T 0715
[0071] Comparative Example 1
[0072] This embodiment provides a polyurethane-carbon nanotube composite modified asphalt mixture, and the specific method is:
[0073] The materials and preparation process are the same as those in Example 1, but the preparation method of the modified asphalt is different. In this example, methylene diphenyl diisocyanate and polypropylene glycol are firstly extruded to obtain a polyurethane modifier, which is then mixed with carbon nanotubes and asphalt by a high-speed shearing machine to obtain a polyurethane-carbon nanotube composite modified asphalt.
[0074] Specifically, the preparation method of polyurethane-carbon nanotube composite modified asphalt is as follows:
[0075] (1) heating the base asphalt to 160° C. to obtain liquid asphalt;
[0076] (2) The polyurethane modifier, carbon nanotubes and liquid asphalt are mixed, and high-temperature shearing is performed at 180° C. and a shear rate of 4000 rpm for 60 minutes to obtain a composite modified asphalt.
[0077] The polyurethane modifier is prepared by extruding methylene diphenyl diisocyanate and polypropylene glycol via a twin-screw extruder. The preparation method of the polyurethane modifier comprises:
[0078] 1) Add polyol to the main silo and add polyisocyanate to the auxiliary silo separately;
[0079] 2) The screw speed of the twin-screw extruder is set to 200 rpm, and the temperature is set to a gradually increasing gradient, covering a temperature range of 120 to 180° C., and heating is performed in sections;
[0080] 3) After the mixture is melt-kneaded, it is granulated and dried to obtain polyurethane modifier particles with a diameter of about 2 to 3 mm.
[0081] Furthermore, a method for preparing a polyurethane-carbon nanotube composite modified asphalt mixture comprises the following steps:
[0082] S1. Dry the granite aggregate and filler at 180°C for 3h in advance;
[0083] S2. Heat and mix the composite modified asphalt with granite aggregate at a mass ratio of 5% at 180° C. for 3 minutes to obtain a mixture; add filler and continue mixing for 2 minutes to obtain a polyurethane-carbon nanotube composite modified asphalt mixture.
[0084] The parameters of the prepared polyurethane-carbon nanotube composite modified asphalt mixture are shown in Table 3.
[0085] Table 3
[0086] project unit Test results Require Test specifications Marshall Strength kN 35.4 / JTG T 0709 Freeze-thaw splitting strength ratio % 89 80 JTG T 0729 Indirect tensile strength MPa 1.45 / AASHTO 322 Dynamic stability mm / times 9871 >3200 JTG F40-2004 Low temperature complete destruction strain με 3084 >2500 JTG T 0715
[0087] Comparative Example 2
[0088] This embodiment provides a polyurethane-carbon nanotube composite modified asphalt mixture, and the specific method is:
[0089] The materials used are the same as those in Example 1, but the preparation method of the modifier is different. In this example, asphalt, methylene diphenyl diisocyanate, polypropylene glycol and multi-walled carbon nanotubes are stirred with a high-speed shearing machine.
[0090] Specifically, the preparation method is as follows:
[0091] (1) heating the base asphalt to 160°C;
[0092] (2) Adding methylene diphenyl diisocyanate, polypropylene glycol and multi-walled carbon nanotubes into asphalt, high-temperature shearing was performed at 180° C. and a shear rate of 4000 rpm for 60 minutes to obtain a composite modified asphalt.
[0093] Furthermore, a method for preparing a polyurethane-carbon nanotube composite modified asphalt mixture comprises the following steps:
[0094] S1. Dry the granite aggregate and filler at 180°C for 3h in advance;
[0095] S2. Heat and mix the composite modified asphalt with granite aggregate at a mass ratio of 5% at 180° C. for 3 minutes to obtain a mixture; add filler and continue mixing for 2 minutes to obtain a polyurethane-carbon nanotube composite modified asphalt mixture.
[0096] The parameters of the prepared polyurethane-carbon nanotube composite modified asphalt mixture are shown in Table 4.
[0097] Table 4
[0098] project unit Test results Require Test specifications Marshall Strength kN 29.3 / JTG T 0709 Freeze-thaw splitting strength ratio % 83 80 JTG T 0729 Indirect tensile strength MPa 1.32 / AASHTO 322 Dynamic stability mm / times 6584 >3200 JTG F40-2004 Low temperature complete destruction strain με 2768 >2500 JTG T 0715
[0099] Comparative Example 3
[0100] This embodiment provides a first group of control asphalt mixtures, and the specific method is as follows:
[0101] Referring to the preparation method of Example 1, the difference is that no carbon nanotubes are added, and the remaining steps are consistent with Example 1 to prepare a polyurethane modified asphalt mixture. The performance test results are shown in Table 5.
[0102] It can be seen from Table 5 that the low-temperature complete failure strain of the polyurethane modified asphalt mixture without carbon nanotubes is low, slightly lower than the specification requirement, which shows that the addition of carbon nanotubes can significantly improve the low-temperature toughness of polyurethane modified asphalt mixture.
[0103] Table 5
[0104] project unit Test results Require Test specifications Marshall Strength kN 27.8 / JTG T 0709 Freeze-thaw splitting strength ratio % 82 80 JTG T 0729 Indirect tensile strength MPa 1.25 / AASHTO 322 Dynamic stability mm / times 5812 >3200 JTG F40-2004 Low temperature complete destruction strain με 2338 >2500 JTG T 0715
[0105] Comparative Example 4
[0106] This embodiment provides a second group of control asphalt mixtures, and the specific method is as follows:
[0107] The preparation method of Example 1 is referred to, except that no modifier is added to obtain an unmodified asphalt mixture. The performance test results are shown in Table 6.
[0108] It can be seen from Table 6 that the polyurethane-carbon nanotube composite modified asphalt is superior to the unmodified asphalt mixture in terms of mechanical strength, high temperature deformation resistance and low temperature toughness, indicating that the polyurethane-carbon nanotube composite modification can significantly improve the performance of asphalt mixture.
[0109] Table 6
[0110] project unit Test results Require Test specifications Marshall Strength kN 11.4 / JTG T 0709 Freeze-thaw splitting strength ratio % 68 80 JTG T 0729 Indirect tensile strength MPa 1.05 / AASHTO 322 Dynamic stability mm / times 2237 >3200 JTG F40-2004 Low temperature complete destruction strain με 2364 >2500 JTG T 0715
[0111] In summary, the polyurethane-carbon nanotube composite modified asphalt in the examples of this application can significantly improve the comprehensive performance of asphalt mixtures, including good mechanical properties, and better high temperature and water damage resistance. The realization of this modification effect is mainly attributed to the formation of a three-dimensional polymer network structure by polyurethane in asphalt. And because the introduction of carbon nanotubes can enhance the network structure in another way, it can improve the crack resistance of polyurethane asphalt. When the material is prone to brittle fracture, carbon nanotubes can effectively disperse external stress, thereby reducing the generation and expansion of cracks, which is specifically manifested as a greater failure strain under low temperature conditions.
[0112] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A polyurethane-carbon nanotube composite modified asphalt mixture, characterized in that: Includes composite modified asphalt, mineral aggregates and fillers; The composite modified asphalt accounts for 4% to 6% of the sum of the weight of the mineral aggregate and the filler; The composite modified asphalt is prepared by modifying asphalt with a polyurethane-carbon nanotube composite modifier, and the mass ratio of the polyurethane-carbon nanotube composite modifier to the asphalt is 20-25:
100.
2. The polyurethane-carbon nanotube composite modified asphalt mixture according to claim 1, characterized in that: The preparation method of the composite modified asphalt comprises: (1) heating the base asphalt to 160°C to obtain liquid asphalt; (2) The polyurethane-carbon nanotube composite modifier is mixed with liquid asphalt, and high-temperature shearing is performed at 170-180° C. and a shear rate of 3000-4000 rpm for 60-90 min to obtain a composite modified asphalt.
3. The polyurethane-carbon nanotube composite modified asphalt mixture according to claim 1, characterized in that: The polyurethane-carbon nanotube composite modifier is prepared by extruding polyisocyanate, polyol and carbon nanotubes through a twin-screw extruder.
4. The polyurethane-carbon nanotube composite modified asphalt mixture according to claim 3, characterized in that: The preparation method of the polyurethane-carbon nanotube composite modifier comprises: 1) Add polyol and carbon nanotubes into the main silo in proportion, and add polyisocyanate into the auxiliary silo alone; 2) Set the screw speed of the twin-screw extruder between 100 and 300 rpm, set the temperature to a gradually increasing gradient, covering a temperature range of 120 to 160 ° C, and perform segmented heating; 3) After the mixture is melt-kneaded, it is granulated and dried to obtain the polyurethane-carbon nanotube composite modifier.
5. The polyurethane-carbon nanotube composite modified asphalt mixture according to claim 3, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes with a diameter ranging from 10 to 50 nm and a length ranging from 1 to 10 μm.
6. The polyurethane-carbon nanotube composite modified asphalt mixture according to claim 3, characterized in that: The polyisocyanate is one or more of methylene diphenyl diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate.
7. The polyurethane-carbon nanotube composite modified asphalt mixture according to claim 3, characterized in that: The polyol is one or more of polypropylene glycol, polyethylene glycol and castor oil.
8. The polyurethane-carbon nanotube composite modified asphalt mixture according to claim 1, characterized in that: The particle size of the mineral aggregate is ≥0.075 mm, and the mineral aggregate is one or more of basalt, limestone and granite.
9. The polyurethane-carbon nanotube composite modified asphalt mixture according to claim 1, characterized in that: The particle size of the filler is less than 0.075 mm, and the filler is one or more of basalt powder, limestone powder and granite powder.
10. The method for preparing a polyurethane-carbon nanotube composite modified asphalt mixture according to claim 7, characterized in that: S1. Dry the mineral aggregate and the filler at 170-180° C. for 2-3 hours in advance; S2, heating and mixing the composite modified asphalt and the mineral aggregate at 170-180° C. for 3-5 minutes to obtain a mixture; S3. Add filler and continue mixing for 2 to 3 minutes to obtain polyurethane-carbon nanotube composite modified asphalt mixture.